2004
DOI: 10.1093/aje/kwh041
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Cancer Risk in Canada

Abstract: The authors conducted a population-based, case-control study of 21,022 incident cases of 19 types of cancer and 5,039 controls aged 20-76 years during 1994-1997 to examine the association between obesity and the risks of various cancers. Compared with people with a body mass index of less than 25 kg/m(2), obese (body mass index of > or = 30 kg/m(2)) men and women had an increased risk of overall cancer (multivariable adjusted odds ratio = 1.34, 95% confidence interval (CI): 1.22, 1.48), non-Hodgkin's lymphoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
2
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(223 citation statements)
references
References 47 publications
15
199
2
6
Order By: Relevance
“…Previous investigations of the relationship of BMI with renal cell carcinoma risk consistently found an association among women, [3][4][5][6][7][8][9]12 and our results support these findings. Our finding of the greatest risk with high level of BMI (i.e., top 10% of BMI) among women is also in agreement with previous studies, 4,8,11,12,18,25 even though the cutpoints for the top 10% of BMI in the present study are, in general, smaller than those found in previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous investigations of the relationship of BMI with renal cell carcinoma risk consistently found an association among women, [3][4][5][6][7][8][9]12 and our results support these findings. Our finding of the greatest risk with high level of BMI (i.e., top 10% of BMI) among women is also in agreement with previous studies, 4,8,11,12,18,25 even though the cutpoints for the top 10% of BMI in the present study are, in general, smaller than those found in previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…This increase cannot be fully explained by early detection of presymptomatic tumors. 2 Overweight and obesity (expressed as body mass index (BMI)) have been consistently associated with an elevated risk of renal cell carcinoma among women, [3][4][5][6][7][8][9] and to a lesser degree, among men. 4,8,[10][11][12] Physical activity was inversely associated with risk of renal cell carcinoma in some, 4,[13][14][15] but not all 8,12,16,17 studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A USA cohort study of transplant candidates found that obesity was an independent risk factor for HCC in patients with alcoholic cirrhosis (OR 3.2) and cryptogenic cirrhosis (OR 11), but not in patients with hepatitis C, hepatitis B, primary biliary cirrhosis or autoimmune hepatitis, when taking account of diabetes and other confounders (Nair et al, 2002). On the other hand, no increased risk of liver cancer due to obesity was evident when adjusting for alcohol intake and other confounders in a population-based case-control study from Canada (Pan et al, 2004) and in a prospective population-based cohort study from Japan (Kuriyama et al, 2005).…”
Section: Diabetes and Hepatocellular Carcinomamentioning
confidence: 93%
“…Excess body weight has proved to be an important risk factor for cancer, including postmenopausal breast cancer and cancers of the kidney, pancreas, colon and endometrium [1][2][3][4]. Obesity-related alterations in the production and metabolism of hormones like insulin, insulin-like growth factor (IGF)-I and sex-steroid hormones have been proposed to explain the link between adiposity and cancer risk [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%